Public Anthropology in the United States and Indonesia - Imam Subkhan (Humaniora, 2019)
This paper discusses the development of public anthropology in the United States and Indonesia. Drawing on literature reviews and archive studies, this article argues that public anthropology needs to be considered as a pragmatic strategy to elevate the position of anthropology in the public realm, and make it relevant to society. As a scholarly concept, public anthropology in Indonesia is not as popular as in the United States relative to applied anthropology. However, its individual and institutional practices have been flourishing in the last decade, including collaborative works and community engagement, publishing scholarship beyond conventional academic forms, active involvement in contemporary human problems, and efforts to influence public policies. To foster Indonesian public anthropology, an academic promotion system that gives more appreciation to public scholarship should be encouraged. Academic anthropologists may also take the initiative to include public anthropology in the anthropology curriculum. Moreover, the Indonesian Anthropological Association (AAI) can facilitate and promote public anthropology in broader public debates, and maintain its active role in defending humanity.